1996
DOI: 10.1002/pro.5560050903
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of the tumor suppressor p16, an ankyrin‐like repeat protein

Abstract: The p16 protein has been identified as a tumor suppressor that functions by inhibiting the cyclin-dependent kinases CDK4 and CDK6. Deletions or point mutations in the p16 gene have been found in a number of human cancers, emphasizing its importance in regulating cell cycle progression. Inhibition by p16 occurs through protein-protein interactions with its targets. This is not surprising, since p16 is thought to contain ankyrin-like repeats, motifs implicated in protein-protein interactions. Our goal was to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
21
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 40 publications
9
21
0
Order By: Relevance
“…The studies here examine participation in the ankyrin domain of repeats on the C-terminus, but not the N-terminus. Although the ellipticity of the Notch ankyrin polypeptides is lower than expected based on crystal structures of other ankyrin repeat proteins, the CD spectra are consistent both in shape and in magnitude with CD spectra of other ankyrin repeat domains (44,(72)(73)(74)(75), including p16, where high-resolution structural data indicate that each ankyrin repeat adopts an ordered ankyrin fold (41,76).…”
Section: Discussionsupporting
confidence: 60%
“…The studies here examine participation in the ankyrin domain of repeats on the C-terminus, but not the N-terminus. Although the ellipticity of the Notch ankyrin polypeptides is lower than expected based on crystal structures of other ankyrin repeat proteins, the CD spectra are consistent both in shape and in magnitude with CD spectra of other ankyrin repeat domains (44,(72)(73)(74)(75), including p16, where high-resolution structural data indicate that each ankyrin repeat adopts an ordered ankyrin fold (41,76).…”
Section: Discussionsupporting
confidence: 60%
“…Tsai and coworkers found this protein to display a steep, cooperative unfolding transition when helix content was monitored by circular dichroism (CD) spectroscopy as a function of guanidine hydrochloride, although the midpoint for the unfolding transition was rather low [46]. Similar results were obtained using urea [47] and thermal denaturation [48]. Later, Itzhaki's group examined the unfolding transition of this protein more extensively [49], and showed that similar unfolding transitions (and fitted thermodynamic parameters) are obtained when urea-induced unfolding is monitored by CD, fluorescence from two N-and C-terminal tryptophans, and gel filtration chromatography The Drosophila Notch ankyrin domain also appears to unfold via a cooperative, all-or-none mechanism.…”
Section: Cooperative Equilibrium Folding Of Repeat Proteinsmentioning
confidence: 61%
“…Despite their modular architecture, several linear repeat proteins have been shown to display two-state equilibrium unfolding, including the four-ankyrin-repeat proteins p16 INK4a and myotrophin, [30][31][32] and the seven-ankyrin-repeat domain from the Drosophila Notch receptor. 33,34 Recently, a three-repeat designed ankyrin domain has been shown to conform to a simple kinetic two-state mechanism.…”
Section: Introductionmentioning
confidence: 99%